The Restitution of the Past: Autofictional Memory in El azul de las abejas by Laura Alcoba (Anclajes, 2021)
The construction of identity in contemporary literature of the self has become a recurring fact in recent years. The limits that blur autofictions, where hazy boundaries separate the real from the fictitious, allow for life experiences to become diluted within the literary experience. Within the context of exile, all forms of identity construction are placed “in transit”: a learning process that involves an adaptation to a new territory and a new language. The second volume in Laura Alcoba's trilogy, El azul de las abejas (2014 [2013]), shows how the exiled subject’s identity is constructed as a result of the changes arising from linguistic configuration and learning.
Keywords: Laura Alcoba; extraterritorial literature in the French language; literary criticism; XXI century; Argentina